Экзистенциальный трагизм мигрантов в нарративах Федора Степуна - Smirnov, Ivan (Studia Rossica Posnaniensia, 2025)
Modern researchers, analyzing the paradigms of global migration processes, focus on the brilliant creative legacy of Fyodor Stepun, a representative of Russian cultural emigration, a religious philosopher, sociologist and publicist, who reflected in his narratives the migration experience of an entire generation. The reasons for the increased demand for Stepun’s philosophical research lie in the philosophical analysis of the existential crisis of a migrating person, which is consonant with today’s realities. Stepun’s thought configurations from the disciplines accompanying philosophy – political science, anthropology, sociology and psychology – are reliably woven into his literary works, the concepts of which strengthen the platform of historiosophical beliefs. Within the framework of the article, the author brings to the forefront a philosophical analysis of the causes of the existential crisis of migrants, as well as meaningful factors in the predictability of migrants’ behavior in the struggle to preserve their national identity in a foreign world.